Clinical Management of Non-alcoholic Steatohepatitis and the Role of the Cardiologist - Carlos Millán-Rodríguez; Carlos Palacios Castelló Palacios Castelló; María de Regla Caballero-Valderrama; Gonzalo Barón Esquivias (European Cardiology Review)
Non-alcoholic fatty liver disease (NAFLD) is a spectrum of fat-associated liver conditions that increase risk of cardiovascular disease and mortality. The diagnosis and clinical management of NAFLD remain a challenge for cardiologists. Our group performed a systematic review in PubMed of the relationship between NAFLD and cardiovascular disease, identifying 35 relevant articles. NAFLD is likely to be the liver’s expression of metabolic syndrome and increases the risk of several cardiovascular diseases, including coronary artery disease, stroke, heart failure and electrical disorders, and chronic kidney disease. Echocardiography is a useful tool to check early subclinical abnormalities in heart structure and function linked to NAFLD progression, such as cardiac diastolic impairment or epicardial fat thickness. Currently, NAFLD is predominantly managed by lifestyle changes with the aim of weight loss, based on the Mediterranean diet and intense exercise training. Despite the lack of approved drugs for NAFLD, new potential treatments, mainly glucagon-like peptide-1 agonists or sodium–glucose cotransporter 2 inhibitors, could change cardiologists’ approach to this pathology.